Spatial Design and Management Guidelines Promoting Human Perception Toward Cultural Environment for Community-Based Tourism: A Case Study of Khlong Daen in Songkhla and Nakhon Si Thammarat Provinces - Patjantavivat, Pimpakarn; Natakun, Boonanan (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This research studies and analyses the human perception towards cultural environments of community and its surrounding areas, reflecting the identity of local cultures having high potentials in promoting tourism. Khlong Daen community located on the border between Songkhla and Nakhon Si Thammarat is selected as a case study. This paper proposes a spatial design and management guidelines promoting human perception towards cultural environments for community-based tourism. This research employs qualitative methods including mental mapping from 2 groups of participants; insiders and outsiders (17 people), coupled with photography and interviews to identify specific physical characteristics of the study areas. Subsequently, analysis results in the forms of collective cultural mappings were assessed by focus group discussions. The study has found that the participants can recognize and perceive cultural environments through participative events and activities in the community. However, there are two differences between insiders’ and outsiders’ viewpoints which are cognitive mappings and sequences of important areas indicated on the mappings. Even though all the participants can recognize tangible and intangible cultural environments as well as some cultural environments that no longer exist the area, all these cultural environments can be categorized into 2 types. They are nodes (mentioned more than 25 percent on all the mappings) and sub nodes (mentioned less than 25 percent on all the mappings). The identified physical elements of the study area can also be used to propose a spatial design and management guidelines that help promote for community-based tourism in Khlong Daen community. Lastly, such a research methodology, techniques and processes presented in this paper could be replicated to study other potential communities in Songkhla and Nakhon Si Thammarat provinces as well as elsewhere to promote cultural tourism organized by the locals.